2021
DOI: 10.3389/fmicb.2021.714726
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Shifts of Microbial Community and Metabolite Profile From Wheat to Mature Daqu

Abstract: Wheat-originated microbes play an important role in shaping the quality of high-temperature Daqu which is commonly used as a starter for producing sauce-flavor Baijiu. However, the shifts of microbiota from raw material to fresh Daqu and then to mature Daqu remain unclear. Hence, in the present study, the inner and outer of fresh and mature Daqu were collected to explore the correlation between microbiota and metabolites as well as the source of the microbiota in Daqu. Results indicated that the activities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…However, there is limited research focusing on the biochemical and quality changes of sturgeon filets during refrigerated storage. Although Zhang Y. et al (2021) , Zhang Z. et al (2021) reported on the microbial changes of sturgeon being stored at ice temperature, only the specific spoilage organisms (SSOs) were evaluated. The effects of biochemical drivers on the bacterial communities and volatile profiles of refrigerated sturgeon filets at 4°C are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is limited research focusing on the biochemical and quality changes of sturgeon filets during refrigerated storage. Although Zhang Y. et al (2021) , Zhang Z. et al (2021) reported on the microbial changes of sturgeon being stored at ice temperature, only the specific spoilage organisms (SSOs) were evaluated. The effects of biochemical drivers on the bacterial communities and volatile profiles of refrigerated sturgeon filets at 4°C are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Daqu is a traditional fermentation starter of soy sauce aroma-type baijiu made of wheat and used throughout the fermentation process of making baijiu [15,30]. Thus, it is the essential material for soy sauce aroma-type baijiu production.…”
Section: Afs and Ota Content In Daqu Samplesmentioning
confidence: 99%
“…However, the microbial composition and physicochemical indices in Daqu undergo continuous succession during production due to environmental factors ( Fu et al, 2021 ). Meanwhile, different microbiotas and physicochemical properties have been observed in different parts of the same Daqu brick due to the difficulty in transferring heat, water, and oxygen ( Jin et al, 2019 ; Chen et al, 2020 ; Zhang Y. et al, 2021 ). The aforementioned results all affect the quality of Daqu .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, analyzing the microbiotas and physicochemical indices inside and outside the Daqu during production might provide a scientific theory for establishing a relatively comprehensive method to evaluate the quality and control the process of Daqu . Some studies on these have been performed ( Jin et al, 2019 ; Chen et al, 2020 ; Zhang Y. et al, 2021 ). Jin et al (2019) revealed that the dominant microbes and volatile flavors on the surface and the core of soy-flavor Daqu had different distribution characteristics and found that microbial interactions were stronger in the core than on the surface ( Jin et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%